Dois ensaios sobre a qualidade regional do capital humano no Brasil - Saraiva, Maurício Vitorino (2016)
Recent studies suggest that regional disparities in the quality of human capital are important in explaining differences in performance of economic growth. However, little has been studied about the spatial distribution of human capital in Brazil and its ability to act as a locational factor for economic activities. To fill this gap, this study proposes the creation of a multidimensional measure of qualitative human capital through Factor Analysis techniques, in addition to using a usual proxy for the quantitative aspect. Thus, it is possible to accompany the accumulation of human capital stock of the population from childhood to adulthood, either in qualitative or quantitative terms. This study is divided in two essays. In the first, the human capital measures were elaborated and a spatial analysis of the stock of quantitative and qualitative human capital was performed in Brazil, at the level of 558 micro-regions between 2009 and 2014. The results allow to draw the distribution map of human capital in the country, suggesting the existence of strong regional disparities: the South and Southeast regions present high quantity associated with high quality; North and Northeast, generally, present lower stocks in quantitative and qualitative aspects, although some micro-regions present high level of quantity that is not accompanied by increased quality; and Midwest presents intermediates and high levels of quantity, while the quality is only intermediate. Therefore, locations with a high quantity of human capital do not necessarily display a higher standard of quality (vice versa). Throughout the analyzed period, there occurred a slight improvement of the human capital’s levels in the country, especially in the quantitative aspect. In the second essay, through a spatial econometric model with panel data between 2009 and 2014 for 254 micro-regions of the South and Southeast regions of Brazil, a study supported on locational models for tertiary sector by level of intensity in knowledge was applied. This methodology allows us to identify the importance of different aspects of human capital in attracting economic activities: the quality of human capital is a locational factor for superior services (knowledge-intensive), while the quantitative aspect attracts both superior (intensive) and traditional services (non-knowledge-intensive).